Activity of Omadacycline Alone and in Combination against Carbapenem-Nonsusceptible Acinetobacter baumannii with Varying Minocycline Susceptibility - Taylor Abbey; Alesia Vialichka; Michele Jurkovic; Mark Biagi; Eric Wenzler (Microbiology Spectrum, 2022)
ABSTRACT Tetracycline-based combinations are increasingly used for serious carbapenem-nonsusceptible Acinetobacter baumannii (CNSAb) infections given their potent in vitro activity, synergism with other agents, and acceptable toxicity profile. Omadacycline is a novel aminomethylcycline with activity against minocycline-resistant pathogens, once daily oral dosing, and favorable pharmacokinetic properties. Given these potential advantages, the in vitro potency and antibacterial activity of omadacycline were evaluated alone and in combination against CNSAb with varying minocycline susceptibility. Broth microdilution testing of 41 CNSAb revealed that omadacycline (MIC50/90: 4/8 mg/L) inhibited 68.3% (28/41) of isolates at ≤4 mg/L and its activity was unaffected by minocycline nonsusceptibility (MIC50/90: 4/8 mg/L; 74.2% [23/31] inhibited at ≤4 mg/L). Ten (5 minocycline susceptible and 5 nonsusceptible) of the 41 CNSAb isolates were then evaluated in time-kill analyses against omadacycline and comparator agents alone and in dual- and triple-drug combinations at the free maximum concentration of drug in serum (fCmax). Amikacin, meropenem, and polymyxin B alone were each bactericidal against 4 of 10 (40%) isolates while omadacycline and sulbactam were bactericidal against 0 (0%) and 1 (10%), respectively. In dual-drug combinations with omadacycline, synergy was observed against 80% of isolates with sulbactam followed by 30% with amikacin or polymyxin B and 0% with meropenem or rifampin. The triple-drug combination of omadacycline, sulbactam, and polymyxin B achieved synergy against just one additional strain over the omadacycline-sulbactam dual combination but significantly reduced the time to 99.9% kill by more than 6 h (4.6 ± 2.8 h vs. 11.3 ± 5.9 h, P < 0.01). These results support the continued investigation into tetracycline-based combinations against CNSAb, particularly those including sulbactam, and suggest that omadacycline may have in vitro advantages over existing tetracycline-derivatives. IMPORTANCE Treatment of infections due to Acinetobacter baumannii often involves the use of multiple antibiotics simultaneously as combination therapy, but it is unknown which antibiotics are best used together. Tetracycline agents such as minocycline and tigecycline maintain good activity against A. baumannii and are often used with one or more other agents to achieve better killing of the bacteria. Omadacycline is a new tetracycline that may have a role in the treatment of A. baumannii, but no data are available evaluating its interaction with other commonly used drugs such as polymyxin B and sulbactam. Therefore, the purpose of this study was to investigate the antibacterial activity of omadacycline when combined with one or more other agents against carbapenem-resistant strains of A. baumannii. These findings may then be used to design confirmatory studies that could help decide what drugs work best together and what combination of agents should be used for patients.